Cellule XIII de Jean Rogissart - Retinskaâ, Tat'âna Ivanovna (Linguistica (Ljubljana), 2018)
Nonconventional lexical units have an important place in the regional novel, and regionalisms dominate among the elements of the marked vocabulary. However, the novel Cellule XIII by Jean Rogissart is considerably different from the works of other regionalist writers. In this study, we propose an analysis of the two following segments of a nonconventional lexical units: 1) local lexemes; 2) lexemes of traditional argot. It is worth noting that the title of the article, which contains the word "fusion", shows the importance of two language subsystems in the narrative: the insertion of territorially restricted units and argotisms into the fabric of a literary text is necessary to identify the speaker and give a more accurate description of events. Rogissart was an Ardennes author who dealt with the theme of war and managed not only to describe the physical and moral sufferings of the people, but also to convey the characteristic features of their compatriots, and thus preserve their linguistic heritage. The study of Rogissart's regional and argotic vocabulary and of its actual use in the novel makes it possible to also see how certain features serve to characterize the linguistic social status of a regional speaker and his or her worldview.
Keywords: argo; francoščina; govor Ardenov; narečja; Rogissart, Jean: Cellule XIII; romani